البـِنية المــَوضُوعاتـيـة في قصيدة حاتم الطائي (وَإِنِّيْ لَعَفُّ الْفَقْرِ، مُشْتَرَكُ الْغِنَى) في ضوء إجراء: التَّشاكُل والتَّبايُن السِّيميائي - Al Jahjah | آل جِهجاه, Al-Jawhara bint Bakhit | الجوهرة بنت بخيت (2023)
This study deals with the analysis of the internal organization of themes in the poem of Hatim Al-Tai (and I am in poverty, the common rich) from the point of view of thematic criticism, using the analogy and semiotic contrast procedure. The study divided themes into three growing units; They are: the theme of recognition, then the theme of resistance, then the theme of transcendence. With the analysis of the network of sub-themes generated by them on the levels of consciousness and subconscious, self and other, presence and absence. It concluded that the theme of fear is the main theme in this poem; which was growing in the deep structure, directing other topics and what constituted symbols on the superficial structure of the text; to make it cohesive. | تعالج هذه الدراسة تحليل التنظيم الداخلي للتيمات في قصيدة حاتم الطائي (و إني لعف الفقر، مشترك الغنى) من وجهة نظر النقد الموضوتاعي مستعينة بإجراء التشاكل و التباين السيميائي. و قد قسمت الدراسة التيمات إلى ثلاث وحدات متنامية؛ هي: تيمة التعرف، ثم تيمة المقاومة، ثم تيمة التعالي؛ مع تحليل شبكة التيمات الفرعية المتوالدة منها على مستويات الوعي و اللاوعي، و الذات و الآخر، و الحضور و الغياب. وقد انتهت إلى أن تيمة الخوف هي التيمة الرئيسة في هذه القصيدة؛ التي كانت تتنامى في البنية العميقة، و توجه الموضوعات الأخرى و ما يشكلها من رموز على البنية السطحية للنص؛ لتجعلها متماسكة.